Critical care nursing : diagnosis and management - Lough, Mary E.; Stacy, Kathleen M.; Urden, Linda Diann (Elsevier, 2014)
Nine sections highlight the alterations seen in critical care and make it easy to understand the unique challenges of critical care nursing. An abundance of learning tools such as Patient Safety Alerts, Evidence-Based Practice boxes, NIC interventions, case studies, Pharmacologic Management boxes, and more give you a better understanding of clinical practice and help you reference vital information quickly and easily. New to this edition: Combined chapter on shock, sepsis and multiple organ dysfunction syndrome makes understanding similar physiologic processes easier. Chapter summaries provide quick study guides by organizing key information in the chapter. New! 6-second, standard ECG strips help you learn to identify wave forms and accurately reflect what you'll use in practice. New equipment information and photos accurately depicts what you'll encounter in a modern critical care unit.